Kegiatan Ecoprint Dalam Pengembangan Motorik Halus Dan Interaksi Sosial Anak Di SLB Athallah Sungai Rumbai - Junil Adri; Muhammad Shadiqi Zeira; Upi Permata Sari; Yusdhika Aditya Pratama; Rayhan Pratama Gozali; Siti Zahra Raihanah (CV. ITTC INDONESIA, 2026)
This study aims to describe the implementation of ecoprint activities in developing fine motor skills and social interaction among children with special needs at SLB Athallah Sungai Rumbai, Dharmasraya Regency, West Sumatra. The study employed a qualitative approach using a descriptive method. The research subjects were students with special needs who participated in the ecoprint activities. Data were collected through observation, documentation, and field notes during the implementation of the program. The ecoprint activity consisted of several stages, including the introduction of tools and materials, identification of various leaves and flowers, arrangement of natural patterns on fabric, printing processes, and evaluation and appreciation of the students' work. The participants were divided into small groups under the guidance of teachers and university students to facilitate learning according to each child's characteristics and abilities. The findings indicate that ecoprint activities create an active and enjoyable learning environment for children with special needs. Activities such as selecting, holding, and arranging natural materials stimulate fine motor development through hand-eye coordination, accuracy, and concentration. Furthermore, group-based activities provide opportunities for students to communicate, collaborate, share tools and materials, and build positive social interactions with peers, teachers, and university student facilitators. The involvement of university students also offers new social experiences that encourage children to become more confident in interacting and expressing themselves. Therefore, ecoprint can serve as an alternative art- and environment-based learning activity that supports the development of fine motor skills and social interaction among children with special needs in special schools.